Gerakan Santri Peduli Lingkungan: Optimalisasi Pengelolaan Sampah di Pondok Pesantren As’ad Kota Jambi - Liani Setyarsih; Septa Pratama; Nadya Bestnissa (Jurnal Medika: Medika, 2025)
Islamic boarding schools (pondok pesantren) as residential educational institutions are characterized by high population density and intensive collective activities, which result in a high volume of waste generation and environmental sanitation problems. These conditions contribute to various health issues, particularly skin diseases such as scabies, which are commonly found in boarding school environments with suboptimal hygiene and waste management. The eco-pesantren program is a strategic approach to improving awareness of health and environmental issues through 3R-based waste management, composting, and environmental education. This community service activity aimed to implement the eco-pesantren program at As’Ad Islamic Boarding School in Jambi City through assistance in waste management practices. The methods applied included a preparation stage involving problem mapping, followed by socialization on environmental health issues, training on waste segregation and processing, and stages of mentoring and evaluation. The results showed an increase in the knowledge and skills of administrators and students in separating organic and non-organic waste, as well as in producing economically valuable products from waste.